The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10534-006-9023-1
|View full text |Cite
|
Sign up to set email alerts
|

Removal of thallium by combining desferrioxamine and deferiprone chelators in rats

Abstract: The hypothesis that two known chelators deferiprone (1,2-dimethy1-3-hydroxypyrid-4-one, L1) and desferrioxamine (DFO) might be more efficient as combined treatment than as monotherapies in removing thallium from the body was tested in rats. Six-week-old male Wistar rats received chelators: L1 (p.o.), DFO (i.p.) or L1 + DFO as 110 or 220 mg/kg dose half an hour after a single i.p. administration of 8 mg Tl/kg body weight in the form of chloride. Serum thallium concentration, urinary thallium and iron excretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A comparison of the results obtained from with and without Chelation therapies indicate that combined (deferasirox þ L 1 ) therapy increases the elimination of Cd effectively, so, removal of Cd is not time dependent at all, also toxicity and side effects of deferasirox and L 1 are very low, therefore after basic preclinical research, they could be recommended for human administration. In comparison to the results obtained by Fatemi et al Amiri et al, 2007;Tubafard and Fatemi, 2008;Fatemi et al, 2009;Tubafard et al, 2010) and our present results, it can be concluded that the two chelators (deferasirox þ L 1 ) are more efficient as combined therapy than single therapy in removing Cd from all tissues.…”
Section: Discussionsupporting
confidence: 77%
“…A comparison of the results obtained from with and without Chelation therapies indicate that combined (deferasirox þ L 1 ) therapy increases the elimination of Cd effectively, so, removal of Cd is not time dependent at all, also toxicity and side effects of deferasirox and L 1 are very low, therefore after basic preclinical research, they could be recommended for human administration. In comparison to the results obtained by Fatemi et al Amiri et al, 2007;Tubafard and Fatemi, 2008;Fatemi et al, 2009;Tubafard et al, 2010) and our present results, it can be concluded that the two chelators (deferasirox þ L 1 ) are more efficient as combined therapy than single therapy in removing Cd from all tissues.…”
Section: Discussionsupporting
confidence: 77%
“…Some of thallium toxicity symptoms which appeared during the period of thallium uptake were the appearance of red staining around the eyes, greenish mottling on the liver, weakness and loss of hair and weight. Also our results shown that iron concentration decreased in blood serum, therefore anemia can occur as a result of iron‐poor dietary intake (iron deficiency anemia) (Amiri et al ., 2007; Fatemi et al ., 2007). During thallium administration, its concentration increased in blood serum while iron level decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Thallium can be released to the environment (Xiao et al ., 2004; Heim et al ., 2002), exposing humans to its noxious effects. For example, it has been reported that thallium can affect several tissues and systems, including the epidermal, gastrointestinal, cardiovascular, reproductive and renal systems (Heim et al ., 2002; Fatemi et al ., 2007; Amiri et al ., 2007). It can also cross the blood–brain barrier, and deposit in the brain, where it causes neurodegeneration, demyelination and the accumulation of end products of lipid oxidation (Galván‐Arzate et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This kind of therapy by combining two chelators is based on the assumption that various chelating agents mobilize toxic elements from different tissue compartments and therefore better results are expected (Flora et al 1995). Results of this kind of combined chelation therapy have been confirmed by Amiri et al (2007), Fatemi et al (2007Fatemi et al ( , 2009), Tubafard and Fatemi (2008). The aim of the present research was to test the chelation potency of deferasirox and deferiprone in combination, given to animals after chromium loading.…”
Section: Introductionmentioning
confidence: 71%
“…These ligands promote the excretion and subsequent depletion of this transition metal in biological systems. Clinical evaluations of some chelators for the removal of toxic metal ions in rats have been previously reported by Amiri et al (2007), Fatemi et al (2007Fatemi et al ( , 2009, Shokooh Saljooghi and Fatemi (2010b), Tubafard and Fatemi (2008). These chelating agents consist of a range of bidentate, tridentate and hexadentate ligands in which two, three or six atoms are able to coordinate, respectively (Clarke and Martell 1992;Gomez et al 1988).…”
Section: Introductionmentioning
confidence: 99%